Investigating EFL children’s task motivation concerning the use of models as written corrective feedback - Luquin, María; García Mayo, María del Pilar (Studies in Second Language Learning and Teaching, 2024)
This study investigated how the inclusion of model texts as a feedback technique affected students’ task motivation and engagement in writing tasks. Adopting a longitudinal design, 60 English as a foreign language (EFL) children (aged 11-12) were divided into three groups: a treatment group, a long-term treatment group, and a control group. The treatment groups received feedback that incorporated model texts as examples of proficient writing, while the control group self-corrected their texts. Task motivation was assessed through self-report questionnaires and focus group interviews. The findings showed that the children responded positively to the use of model texts, particularly those children who had been exposed to this type of feedback over a longer period. While some expressed a preference for more explicit error correction, their overall enjoyment, improvement, as well as enthusiasm for collaborative work highlight the value of integrating model texts into the EFL classroom. Based on these findings, pedagogical implications will be discussed.